A construção das territorialidades das jovens rurais egressas dos cursos de Agronomia e de Pedagogia da UFFS/Campus Erechim e o processo de sucessão na agricultura familiar - Eduardo, Daiane Carla Bordulis (2019)
The study was carried out with young rural women graduated in the Agronomy and Pedagogy courses at UFFS, Erechim-RS Campus. In this research, we sought to understand the participation of the young graduates of the UFFS in the process of succession in the family agriculture. We start from the hypothesis that the formation at higher level could contribute in the processes of succession in the familiar agriculture, mainly by the rural young agronomists. In order to develop the analysis, we worked with the young rural people who identified themselves as such, they entered in the period from 2010 to 2014, between the age group of 15 to 29 years. We used as methodological procedures, for the production of these informations, qualitative and quantitative methods, with the application of questionnaires and interviews with the young rural women. In order to understand the trajectory of higher education and the course of the juvenile territoriality of the students, we consider the theoretical elements on rural youth, using the geographic territorial approach, a tool that offered us the analytical support necessary to study the gender issues in geography, considering as presuppositions the spatial aspects and operative power relations intrinsic to the researched subjects. The problems faced in family agriculture and the challenges of succession by the part of the young people, were analyzed from the perspective of the territoriality of patriarchy and the conflicts of generation, realities that are present in family farming and that contribute in the decision about the permanence in the field. The research showed that the lack of autonomy to implement changes in the family unit of production, economic difficulties faced by farmers and vocational training can help young women to plan their futures outside the rural establishment. Thus, the conflicts involving rural women appear in both courses: agronomists recognize these inequalities towards rural women and seek to conquer their spaces, facing prejudice both in the course itself and also in the labor market. Pedagogues have shown that they are satisfied with their higher education because they have a large presence of women and because they are gaining autonomy, although with little possibility of succession in family agriculture. In this way, we evidence that for the succession in family farming, a geographic analysis, in interaction with other areas of knowledge, is of great relevance in order to process the changes in the field and in the ruralurban relations sought by the young women, in the sphere of the cultural and political-economic dimensions (valued by the research).